Analisis Al-Jam'u Wa Taqsim Pada Surah-Surah Di Al-Qur'an Dalam Juz 30 - Pratama, Firman Afrian; Putri, Adilla Cahyani; Fairuz, Nur Nadya (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2023)
the ability to express thoughts or feelings in language that can be understood and beautiful to feel is a gift from God that not everyone can do. In badi sciences, not only pays attention to the aspect of understanding, but also pays attention to the beauty side. This study aims to find out the analysis of Al jam'u wa taqsim in the verses of the Qur'an by studying and analyzing objects in the verses of the Qur'an and research using a method with a descriptive qualitative approach so that it is more thorough, broad and deep in the research process, s for the results, there is al jam'u wa taqsim in surah surah an-naziat 35-41,surah al-insyiqaq 6-12,al-lail 4-10,al zalzalah 6-8, surah al humazah 1-2,al maun 1-7, al kafirun ayat 6